Weighing the galactic dark matter halo: A lower mass limit from the fastest halo star known - Przybilla, Norbert; Tillich, Alfred; Heber, Ulrich; Scholz, Ralf-Dieter (Astrophysical Journal, 2010)
The mass of the Galactic dark matter halo is under vivid discussion. A recent study by Xue et al. revised the Galactic halo mass downward by a factor of ∼2 relative to previous work, based on the line-of-sight velocity distribution of ∼2400 blue horizontal-branch (BHB) halo stars. The observations were interpreted with a statistical approach using cosmological galaxy formation simulations, as only four of the six-dimensional phase-space coordinates were determined. Here we concentrate on a close investigation of the stars with the highest negative radial velocity from that sample. For one star, SDSSJ153935.67+023909.8 (J1539+0239 for short), we succeed in measuring a significant proper motion, i.e., full phase-space information is obtained. We confirm the star to be a Population II BHB star from an independent quantitative analysis of the Sloan Digital Sky Survey (SDSS) spectrum - providing the first non-LTE (NLTE) study of any halo BHB star - and reconstruct its three-dimensional trajectory in the Galactic potential. J1539+0239 turns out to be the fastest halo star known to date, with a Galactic rest-frame velocity of 694+300-221 km s-1 (full uncertainty range from Monte Carlo error propagation) at its current position. The extreme kinematics of the star allows a significant lower limit to be put on the halo mass in order to keep it bound, of Mhalo ≥ 1.7+2.3-1.1 × 1012 M⊙. We conclude that the Xue et al. results tend to underestimate the true halo mass as their most likely mass value is consistent with our analysis only at a level of 4%. However, our result confirms other studies that make use of the full phase-space information.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Dark matter; Galaxy: halo; Stars: atmospheres; Stars: horizontal-branch; Stars: kinematics and dynamics; Stars: Population II